Uma Proxy para a prevalência de armas de fogo baseada em painel de dados dos Estados Unidos - Daniel Cerqueira; Danilo Santa Cruz Coelho; John J. Donohue; Marcelo Fernandes; Jony Arrais Pinto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– There is a consensus that the proportion of suicides committed with a firearm is the best proxy for gun ownership prevalence. Cerqueira et al. (2018) exploit the socioeconomic characteristics of suicide victims in order to develop a new and more refined proxy. It is based on the fixed effects of the victim's place of residence estimated from a discrete choice model for the likelihood of committing suicide with gun. We empirically assess this new indicator using gun ownership data from the Behavioral Risk Factor Surveillance System (BRFSS) and suicide registers of the US National Center for Health Statistics (NCHS) from 1995 through 2004. We show that this alternative proxy correlates more with the percentage of households with firearms than the conventional proxy based on the proportion of suicides committed with a firearm.
Keywords: K42; 330; crime; firearm; fixed effects; logit; panel data; suicide; violence